1995
DOI: 10.1017/s0033291700037491
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cognitive functioning during spontaneous dieting

Abstract: SYNOPSISIn one of a continuing series of studies, the cognitive performance of normal weight female dieters was compared on two sessions, 3 weeks apart. Those who reported themselves as being on a weight-reducing diet on only one of the two sessions displayed poorer vigilance performance, slower reaction times and poorer immediate recall of words when they were dieting. In contrast, performance on a low processing load tapping task was unaffected. Self-report measures showed that dietary restraint, but not sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
2
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 17 publications
(28 reference statements)
4
64
2
1
Order By: Relevance
“…Whereas poorer immediate memory was found in the short-term, self-imposed dieting studies, 3,5 no such change was found with long-term caloric restriction in either this study or the Minnesota study. 13 Rather, in this study recall performance signi®cantly improved at the end of caloric restriction ( 24%) and then readily reversed to baseline levels upon restoration of suf®cient calories to maintain body weight.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Whereas poorer immediate memory was found in the short-term, self-imposed dieting studies, 3,5 no such change was found with long-term caloric restriction in either this study or the Minnesota study. 13 Rather, in this study recall performance signi®cantly improved at the end of caloric restriction ( 24%) and then readily reversed to baseline levels upon restoration of suf®cient calories to maintain body weight.…”
Section: Discussioncontrasting
confidence: 72%
“…13 Rather, in this study recall performance signi®cantly improved at the end of caloric restriction ( 24%) and then readily reversed to baseline levels upon restoration of suf®cient calories to maintain body weight. It could be that if changes in immediate memory occur, as reported in the earlier studies, 3,5 they occur only during the early weeks of dieting. In this study, subjects with the greatest body weight loss after 5 weeks of caloric restriction had the lowest two second word recall scores (r 0.72, P 0.004), however, this relationship was not found after 10 or 15 weeks of caloric restriction.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The main finding of the present study was the replication of the impairment in cognitive function among unsupported dieters, relative to supported dieters or non-dieting controls, within the first week of attempted weight loss (7,15) . Primarily, the impairments appear to be in tasks which assess the capacity of the central executive and phonological loop components of working memory (12) , although simple reaction speed also appeared to be impaired in unsupported dieters during the early stages of weight loss (6) .…”
Section: Discussionsupporting
confidence: 48%